An Overview of Current Approaches and Challenges to the Control of Endemic Infectious Cattle Diseases in Albania - Koleci, Xhelil; Lilo, Ali; Papa, Sotiraq; Margariti, Keti; van Roon, Annika; Santman-Berends, Inge; van Schaik, Gerdien; Hodnik, Jaka Jakob; Strain, Sam; Guelbenzu-Gonzalo, Maria; Karalliu, Esa (Frontiers in Veterinary Science, 2021)
Agriculture is an important production sector in Albania that makes a significant contribution to the gross domestic product (GDP) and employment. The livestock sector contributes more than half of the agricultural GDP. The Albanian cattle population represents 50% of the total livestock units and accounts for 85% of the national milk production, the rest being supplied by small ruminants. Cattle productivity, health and welfare are hindered by infectious diseases, some of which are also transmissible to humans (zoonosis). The aim of this manuscript is to provide an overview of the control of selected regulated and non-EU regulated cattle diseases in Albania and to highlight specific challenges for the Albanian cattle industry. The most important infectious cattle diseases in Albania for which national control and eradication strategies are in place are bovine brucellosis, bovine tuberculosis, and anthrax, which are all zoonotic. Additionally, lumpy skin disease recently emerged in the Balkan region and is currently subject to controls. Most of the available funds and European Union support are allocated to the control of EU regulated zoonotic diseases. For control of non-EU regulated cattle diseases, no funds are available resulting in the lack of national control programmes (CPs). Based on research, clinical investigations and laboratory results, several non-EU regulated cattle infectious diseases appear endemic in Albanian dairy farms. While no national CPs exist for any of them, regional initiatives are available on a voluntary basis to control infectious bovine rhinotracheitis and bovine viral diarrhea. In the voluntary CPs, there is no monitored requirement to prove disease freedom of purchased animals and to re-evaluate the herd's free status after the introduction of animals into a herd. Data on animal movements that are routinely collected could potentially be used to control the risk of purchase, but quality needs to be further improved to increase its usefulness in disease CPs. This overview aims to collate existing information on the CPs implemented in Albania and to evaluate these to highlight gaps and threats in disease control, as well as opportunities and strengths through a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, with the goal of providing a framework for the future implementation of animal disease control measures in Albania.